Prothrombotic genotypes and risk of major bleeding in patients with incident venous thromboembolism - Johnsen, Håkon Sandbukt; Bjøri, Esben; Hindberg, Kristian; Brækkan, Sigrid Kufaas; Morelli, Vania Maris; Hansen, John-Bjarne (Thrombosis Research, 2020)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Background - Genotypes associated with venous thromboembolism (VTE) may protect against bleeding due to a hypercoagulable state. Whether the risk of major bleeding is reduced in parallel with an increasing number of prothrombotic genotypes during anticoagulant treatment in VTE remains unknown. Objectives - To investigate the association between multiple prothrombotic genotypes and risk of major bleeding in patients with VTE. Methods - Patients with incident VTE ( n = 676) derived from the Tromsø Study were genotyped for rs6025 (F5), rs1799963 (F2), rs8176719 (ABO), rs2066865 (FGG) and rs2036914 (F11) single nucleotide polymorphisms (SNPs). Major bleeding events were recorded during the first year after VTE according to the International Society on Thrombosis and Haemostasis criteria. Cox-regression was used to calculate hazard ratios with 95% confidence intervals (CIs) for major bleeding adjusted for age, sex and duration of anticoagulation according to individual prothrombotic SNPs and categories of risk alleles (5-SNP score; 0–1, 2, 3 and ≥4). Results - In total, 50 patients experienced major bleeding (incidence rate: 9.5/100 person-years, 95% CI 7.2–12.5). The individual SNPs and number of risk alleles were not associated with major bleeding risk. The hazard ratios for major bleeding per category increase of genetic risk score were 1.0 (95% CI 0.8–1.3) for the total study population and 1.1 (95% CI 0.8–1.5) when patients with active cancer were excluded. Analyses restricted to the first 3 months after VTE yielded similar results. Conclusion - Our findings suggest that an increasing number of prothrombotic risk alleles is not protective against major bleeding in VTE patients during anticoagulation.